Halal MSME Empowerment Model through Sharia Financing Scheme and Crowdfunding Technology in the Digital Economy Ecosystem - M. Maulana Aziz Purwanto; Ahmadun Najah (Maaliyah: Journal of Islamic Economic Law and Islamic Finance, 2026)
The halal MSME sector plays a critical role in national economic development due to its substantial contribution to job creation, business innovation, and value-based economic growth. Nevertheless, halal MSMEs continue to face structural challenges, particularly limited access to Sharia-compliant financing, low levels of Islamic financial literacy, and weak engagement with digital platforms for marketing and business expansion. This study aims to analyze a comprehensive empowerment model for halal MSMEs through the integration of Sharia financing schemes with technology-based crowdfunding as an alternative instrument for capital reinforcement and financial inclusion. This research employs a descriptive qualitative method with a literature-based approach, drawing on DSN-MUI fatwas, OJK regulations, and real-world practices of Islamic crowdfunding platforms in Indonesia. The findings indicate that combining Sharia contracts such as murabahah, mudharabah, musyarakah, and ijarah with digital crowdfunding mechanisms can create fair, transparent, and interest-free financing solutions. Furthermore, the proposed empowerment model, which encompasses partnership-based Sharia financing, digital crowdfunding utilization, and the enhancement of halal and digital literacy, has strong potential to strengthen the competitiveness of halal MSMEs within the digital economy ecosystem. This model offers an effective strategy for fostering business independence and advancing the development of Indonesia's Sharia economic landscape.